Armies and political change in Britain, 1660-1750 - Smith, Hannah 1976- (Oxford scholarship online, 2021)
'Armies and Political Change in Britain, 1660-1750' explores significant continuities and developments in the armed forces across the reigns of seven monarchs, using a vivid and extensive array of archival, literary, and artistic material to present a new perspective on the political and military history of Britain